Tiagabine-induced encephalopathy suppressed by vagus nerve stimulation: A case report - Christine N. Smith; Stephan Eisenschenk; Yue Wang (Epilepsy & Behavior Reports)
Tiagabine has been associated with reports of status epilepticus as well as encephalopathy, even when used within therapeutic doses. Vagus nerve stimulation (VNS) has been used successfully to reduce seizure frequency in the outpatient setting as well as in the acute setting of status epilepticus. It is also theorized to reduce cortical synchronization. We present a case of a patient on adjunctive tiagabine therapy who developed sudden onset encephalopathy and rhythmic delta activity soon after vagus nerve stimulation was turned off in preparation for magnetic resonance imaging. The bilateral rhythmic delta activity significantly reduced in burden after VNS was turned back on and encephalopathy also gradually improved to baseline. We hypothesize that vagus nerve stimulation successfully interrupted diffuse hypersynchrony, in the form of bilateral rhythmic delta activity, caused by tiagabine. To our knowledge, this is the first report of such a phenomenon.